2013
DOI: 10.1186/1471-244x-13-194
|View full text |Cite
|
Sign up to set email alerts
|

Gastro oesophageal reflux disease (GORD)-related symptoms and its association with mood and anxiety disorders and psychological symptomology: a population-based study in women

Abstract: BackgroundPsychopathology seems to play a role in reflux pathogenesis and vice versa, yet few population-based studies have systematically investigated the association between gastro-oesophageal reflux disease (GORD) and psychopathology. We thus aimed to investigate the relationship between GORD-related symptoms and psychological symptomatology, as well as clinically diagnosed mood and anxiety disorders in a randomly selected, population-based sample of adult women.MethodsThis study examined data collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
(51 reference statements)
1
23
0
1
Order By: Relevance
“…Our study reports a higher prevalence of GERD than previous Australian studies, 3,4 but is consistent with the prevalence data reported in recent clinical studies. 5,13 This discrepancy may relate to the use of a different GERD measure administered by general practitioners and the inclusion of younger men and women. 3 It may also reflect recent observations of secular increases in upper gastrointestinal chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study reports a higher prevalence of GERD than previous Australian studies, 3,4 but is consistent with the prevalence data reported in recent clinical studies. 5,13 This discrepancy may relate to the use of a different GERD measure administered by general practitioners and the inclusion of younger men and women. 3 It may also reflect recent observations of secular increases in upper gastrointestinal chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of affective disorders on GERD have been inconsistent, with some showing no effect, while others have shown a positive and even a negative effect on GERD . Furthermore, most previous research on GERD and affective disorders have been conducted in clinical settings in patients with a high‐degree of comorbidity and consequent limited applicability to the general population …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated factors for GORD are broadly classified into genetic, demographic, behavioural and comorbid factors [6]. Psychological stress predisposes to GORD [7,8] by causing barrier dysfunction of gastrointestinal mucosa and permeability defect in oesophageal stratified epithelia [7]. Also, spicy food, carbonated soft drinks, coffee, tea and irregular dietary habits were found associated with GORD symptoms [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of these studies diagnosed psychological distress based on medical records or self-reported symptom scales, whereas other studies did not document the diagnosis of reflux with objective testing, rather making the diagnosis of reflux based on the patient's complaint or on medical history [22,23,24,25,26,27]. Thus, the results of these studies could have potential biases related to lack of proper diagnosis of either psychological disorders or reflux problems.…”
Section: Discussionmentioning
confidence: 99%